2017
DOI: 10.1101/234286
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Arabidopsis leaf hydraulic conductance is regulated by xylem-sap pH, controlled, in turn, by a P-type H+-ATPase of vascular bundle sheath cells

Abstract: The leaf vascular bundle sheath cells (BSCs) that tightly envelop the leaf veins, are a selective and dynamic barrier to xylem-sap water and solutes radially entering the mesophyll cells. Under normal conditions, xylem-sap pH of <6 is presumably important for driving and regulating the transmembranal solute transport. Having discovered recently a differentially high expression of a BSC proton pump, AHA2, we now test the hypothesis that it regulates this pH and leaf radial water fluxes.We monitored the xylem… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 72 publications
(115 reference statements)
0
29
0
Order By: Relevance
“…(c) When the activity of H + ‐ATPases in the bundle sheath cells is inhibited, xylem alkalization decreases the Pf, and as a consequence, K leaf is low (blue arrows). Figure from Grunwald et al (2021).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…(c) When the activity of H + ‐ATPases in the bundle sheath cells is inhibited, xylem alkalization decreases the Pf, and as a consequence, K leaf is low (blue arrows). Figure from Grunwald et al (2021).…”
Section: Figurementioning
confidence: 99%
“…If the barrier mechanism of bundle sheath cells is regulated by the pH of xylem sap, they thought that AHA2 would be an interesting candidate gene to characterize. Therefore, they investigated the effects of AHA2 on the pH of xylem sap and on leaf hydraulic conductance, and the results of this study are reported in this issue of TPJ (Grunwald et al ., 2021).…”
Section: Figurementioning
confidence: 99%
“…Transcripts encoding three tonoplast intrinsic proteins (TIP1.1, TIP1.2 and TIP2.2) also accumulated preferentially in bundle sheath cells (Figure 2A), presumably allowing water storage in the large vacuole. Lastly, in addition to these transporters, specific P-type and V-type ATPases that could regulate leaf hydraulic conductance (Grunwald et al, 2021) and establish a proton gradient across plasma and vacuole membranes to power secondary transport were strongly expressed in bundle sheath cells (Supplemental Figure 3B). Taken together, this preferential patterning of multiple aquaporins to the rice bundle sheath suggests an important role for these cells associated with water transport and storage.…”
Section: Patterning Of Gene Expression In the Rice Bundle Sheath Conditions The Cells For Water Transportmentioning
confidence: 99%
“…Plant types. We used WT (wild type) Arabidopsis thaliana plants ecotype Colombia, Col-0 (aka Col), the T-DNA insertion AHA2 mutants aha2-4 (SALK_ 082786) (Col) and aha2-4 complemented with SCR: AHA2 (line 56) (Col), and SCR:GFP (Col) as already described (Grunwald et al, 2021). In addition, we used WT Arabidopsis (Col) with the Glabrous mutation (WT Col-gl), phot1-5 (nph1-5) (Col-gl), phot 2-1(npl1-1 or cav1-1) (Col-gl) and the double mutant phot1-5phot2-1 (nph1-5 npl1-1) (Col-gl) (Kagawa et al, 2001), which were kindly provided by the Ken-Ichiro Shimazaki lab (Tokyo, Japan).…”
Section: Plant Materialsmentioning
confidence: 99%
“…In the past decade, it has been established that the bundle sheath cells (BSCs), a parenchymatous layer which tightly enwraps the entire leaf vasculature, can act as a dynamic and selective xylem-mesophyll barrier to water and ions, which participates in Kleaf regulation (Shapira et al, 2009;Shatil-Cohen and Moshelion, 2012;Wigoda et al, 2014Wigoda et al, , 2017Grunwald et al, 2021). Moreover, we recently discovered that the BSCs' H + -ATPase proton pump, AHA2, participated in regulating Kleaf via changes in the xylem pH and the positive correlation between AHA2-driven xylem acidification and Kleaf was due to an increase in the osmotic water permeability of the BSCs membrane (Grunwald et al, 2021). AHA2 is expressed particularly abundantly in the BSCs (at an over-three-fold higher level as compared to the neighboring mesophyll cells; Wigoda et al, 2017, GEO repository Experiment GSE85463), explaining how such acidification is possible.…”
Section: Introductionmentioning
confidence: 99%